2011
DOI: 10.1097/igc.0b013e31821dd3b2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus Infection in Women in Portugal

Abstract: This is the first population-based study to quantify and describe cervical HPV infection in mainland Portugal. This study provides baseline data for future assessment of the impact of HPV vaccination programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
5
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
1
16
5
3
Order By: Relevance
“…In our study, in spite of the limited sample size, we found no difference in ST and MT prevalence comparing women with CIN1 with those with CIN2 or worse. By contrast, Pista et al [12], studying Portuguese women, found a significant association between MT infections and disease severity. Argyri et al [11] also found that MT infections were significantly more common in women with squamous intraepithelial lesions compared with healthy women.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our study, in spite of the limited sample size, we found no difference in ST and MT prevalence comparing women with CIN1 with those with CIN2 or worse. By contrast, Pista et al [12], studying Portuguese women, found a significant association between MT infections and disease severity. Argyri et al [11] also found that MT infections were significantly more common in women with squamous intraepithelial lesions compared with healthy women.…”
Section: Discussionmentioning
confidence: 87%
“…MT-HPV has been observed in women with persistent infections, but its relationship with cervical carcinogenesis has not been established [12]. Importantly, there is no consensus whether MT-HPV infections harbouring HPV16/18 and other HPV types are associated with higher risk of carcinogenesis than ST-HPV16/18 infections [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Jaisamrarn found a paradoxical result that co-infection could increase the risk of progression to a CIN but also increase the chance of clearance [ 13 ]. Pista, studying Portuguese women, found a significant association between multiple infections and disease severity [ 14 ]. Balbi et al concluded that the infection with multiple HPV types is a significant risk factor for high-grade CIN [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HR-HPV infection was increased in women who reported at least two sexual partners. The CLEOPATRE study included women aged 18–64 years in Spain and Portugal [22,23]. The highest prevalence of HR-HPV was observed in women aged 18–24 years (27.0–28.8%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…The CLEOPATRE study included women aged 18–64 years in Spain and Portugal [22,23]. The highest prevalence of HR-HPV was observed in women aged 18–24 years (27.0–28.8%) [23]. The lifetime number of sexual partners was a strong predictor of HPV infection (OR 5.44 for 5–10 partners versus one partner; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%